The Reflection of Diego Pérez De Mesa About Person and Family in the Political-Legal Debate in the Siglo De Oro (Italian Review of Legal History, 2024)
The contribution intends to propose to legal-political historiography the multifaceted figure of Diego Pérez De Mesa (for a short period also Viceroy of the Kingdom of Naples in 1620), author of a treatise dedicated to the legal and political foundations of state sovereignty
Keywords: razon de estado; servi natura; Pérez de Mesa